Development of Psychomotor Assessment Strategies and Instruments: A Comprehensive Approach to Improving Learning Quality (Jurnal Sustainable, 2024)
Psychomotor assessment is an important aspect of education that focuses on students' physical abilities and motor skills. This study aims to examine the development of psychomotor research strategies, techniques and instruments that are valid, reliable, and in accordance with learning needs. The research method used was a literature study with descriptive analysis techniques from various related literature sources. The results showed that psychomotor assessment requires a comprehensive approach involving various techniques, such as tests, observations, performance assessments, portfolios, and products. The development of standardized and accurate assessment instruments such as assessment rubrics is an important step to ensure the validity and reliability of the assessment. Although there are challenges in assessing the psychomotor domain such as limited instruments and difficulties in objective assessment. The limitations of this study lie in the use of the literature study method which limits the scope of the study only to the available literature without involving data in the field or direct interviews with educators. For further research, it is hoped that it can conduct trials of psychomotor assessment instruments in real conditions in various types of education and involve more diverse respondents to increase the validity and reliability of the instrument.